Positive electrode material for lithium ion secondary battery and preparation method of positive electrode material
By doping transition metal oxides on the polycrystalline particles and grain boundary interfaces of the ternary positive electrode material, a detailed and dense structure is formed, which solves the problem of insufficient performance of the ternary positive electrode material and improves the electrochemistry and chemistry of lithium-ion secondary batteries. Mechanical properties and reduce production costs.
Patent Information
- Application Number
- CN202310891343.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-30
- Filing Date
- 2023-07-19
- Publication Date
- 2024-12-31
AI Technical Summary
The prior art cannot effectively modify the ternary positive electrode material, resulting in insufficient electrical and mechanical properties in lithium-ion secondary batteries and high industrial production costs.
A ternary positive electrode material with a polycrystalline particle structure and doped with positive 5-valent or positive 6-valent transition metal oxides, such as tungsten oxide, niobium oxide or molybdenum oxide, through primary sintering and di- The subsintering process forms a refined and dense particle structure.
It improves the mechanical strength and high-temperature cycle stability of the ternary positive electrode material, reduces the impedance growth of the battery during the cycle, and significantly improves the electrochemical performance of the battery.
Smart Images

Figure CN119230735A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion secondary batteries, and in particular to a positive electrode material for lithium ion secondary batteries and a preparation method thereof. Background Art
[0002] In recent years, with the continuous development of electronic technology, people's demand for battery devices used to support the energy supply of electronic devices has been increasing. Nowadays, batteries that can store more electricity and output high power are needed. Traditional lead-acid batteries and nickel-metal hydride batteries can no longer meet the needs of new electronic products. Therefore, metal batteries have attracted more widespread attention. In the process of developing metal batteries, their capacity and performance have been effectively improved. In the prior art, metal batteries include lithium-ion batteries, anode-free batteries, lithium metal batteries, sodium metal batteries, sodium ion batteries, potassium metal batteries, potassium ion batteries, magnesium metal batteries, magnesium ion batteries, zinc ion batteries or zinc metal batteries. Among them, lithium metal batteries are widely developed and used due to their excellent electrochemical properties and cycle retention rate.
[0003] The positive electrode materials of the lithium-ion secondary batteries currently used usually include lithium cobalt oxide (LiCoO2), ternary materials (LiNi x Co y Mn 1-x-y O2, NCM), lithium iron oxide (LiFePO4), nickel cobalt aluminum oxide (NCA) and sulfide (Li-S). Lithium cobalt oxide is a relatively mature, stable and reliable positive electrode material, which can provide high capacity and long cycle life, but its disadvantages are high price and potential safety hazards. Lithium iron oxide has good safety, is not easy to explode under overcharge, over discharge, impact and other conditions, and has a long life. However, its energy density is too low and its volume is too large. The advantage of sulfide as a positive electrode material is that it has a large storage capacity and can theoretically achieve a very high energy density. However, its cycle life is short, and in practical applications, problems such as structural mismatch and multiple reaction products need to be solved. Nickel cobalt aluminum oxide is widely used in automotive batteries, which has good electrical conductivity and durability, but its cost is high. In the prior art, the more commonly used positive electrode material is a ternary positive electrode material, which has a higher energy density and power density, and a relatively long cycle life. However, ternary positive electrode materials, especially nickel cobalt manganese oxide lithium materials, still have problems such as particle breakage caused by insufficient mechanical strength and unsatisfactory electrical performance during use.
[0004] In order to solve the shortcomings of ternary positive electrode materials, the prior art generally adopts a method of modifying ternary positive electrode materials, such as nickel cobalt manganese oxide, to make them have better performance. For example, in one method, the ternary positive electrode material can be placed in a gas atmosphere of tungsten oxide, and the tungsten oxide is deposited on the surface of the ternary positive electrode material by cooling, thereby forming a single crystal ternary positive electrode material coated with metal tungsten oxide in the gas phase. In another method, the precursor of the ternary positive electrode material can be first mixed with a lithium source, and then a single crystal structure of a nickel-rich ternary positive electrode material can be obtained after calcination; then the single crystal structure of the nickel-rich ternary positive electrode material is mixed with a tungsten source, sintered, and cooled, thereby obtaining a tungsten-coated and doped single crystal nickel-rich ternary positive electrode material.
[0005] However, these methods in the prior art can only modify the ternary positive electrode materials of the single crystal structure, and cannot modify the ternary positive electrode materials of the polycrystalline structure. In addition, the process of the method in the prior art is relatively complicated, and because the melting point of oxidized tungsten is relatively high (about 1837°C), it is necessary to heat the tungsten oxide gas atmosphere to a very high temperature, so it is highly dependent on energy consumption, and the cost is high during large-scale industrial production. In the method using the secondary sintering process, the addition of a tungsten source during the second sintering does not significantly improve the electrochemical properties of the ternary positive electrode material. Therefore, it is necessary to develop a positive electrode material for lithium-ion secondary batteries and a preparation method thereof to improve the deficiencies in the prior art. Summary of the invention
[0006] The main purpose of the present invention is to provide a positive electrode material for lithium ion secondary batteries and a preparation method thereof, so as to solve the problem that the methods in the prior art cannot effectively modify the ternary positive electrode material to obtain the desired electrical and mechanical properties.
[0007] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a positive electrode material for a lithium-ion secondary battery is provided, comprising: polycrystalline particles of a ternary positive electrode material, comprising a plurality of primary particles; and a modifying material, located on the surface of the polycrystalline particles and / or on the grain boundary interface between the primary particles, the modifying material comprising an oxide of a transition metal with a positive valence of five or six.
[0008] Furthermore, in the above-mentioned positive electrode material, the modifying material comprises tungsten oxide, niobium oxide or molybdenum oxide.
[0009] Furthermore, in the above-mentioned positive electrode material, the primary particles have a particle size of 400 nm or less.
[0010] Further, in the above-mentioned positive electrode material, an average particle diameter of the primary particles is in the range of 250 nm to 350 nm.
[0011] Furthermore, in the above-mentioned positive electrode materials, the ternary positive electrode material has a chemical formula of LiNix Co y Mn 1-x-y O₂, where 0.8 ≤ x < 1, 0 < y < 1 and 0 < x + y < 1; preferably 0.9 ≤ x < 1, 0 < y < 1 and 0 < x + y < 1.
[0012] Furthermore, in the above positive electrode material, the doping depth of the modification material is in the range of 0 nm to 20 nm.
[0013] Furthermore, in the above positive electrode material, based on the total number of atoms of the positive electrode material, the doping amount of the transition metal in the positive electrode material is in the range of 0.25 atomic % to 2.1 atomic %.
[0014] According to another aspect of the present invention, there is provided a method for preparing a positive electrode material for a lithium ion secondary battery, comprising the following steps: Step S1, subjecting a lithium source, a ternary positive electrode material precursor and a modification material to a first sintering, wherein the modification material comprises an oxide of a transition metal with a valence of +5 or +6; Step S2, grinding the product after the first sintering and subjecting the ground product to a second sintering, wherein the temperature of the first sintering is lower than the temperature of the second sintering.
[0015] Furthermore, in the above method, the ternary positive electrode material precursor is [Ni x Co y Mn 1-x-y (OH)₂, where 0.8 ≤ x < 1, 0 < y < 1 and 0 < x + y < 1; preferably 0.9 ≤ x < 1, 0 < y < 1 and 0 < x + y < 1.
[0016] Furthermore, in the above method, the modification material comprises tungsten oxide, niobium oxide or molybdenum oxide.
[0017] Furthermore, in the above method, the molar ratio of the ternary positive electrode material precursor to the modification material is in the range of 100:0.25 to 100:2.0.
[0018] Furthermore, in the above method, the first sintering is carried out at a temperature in the range of 450 °C to 600 °C for 4 to 7 hours, and oxygen is introduced at a flow rate of 80 ml / min to 150 ml / min during the first sintering.
[0019] Furthermore, in the above method, the second sintering is carried out at a temperature in the range of 700 °C to 800 °C for 12 to 20 hours, and oxygen is introduced at a flow rate of 80 ml / min to 150 ml / min during the second sintering.
[0020] Furthermore, in the above method, the lithium source comprises lithium hydroxide or lithium carbonate.
[0021] Furthermore, in the above method, the molar ratio of the ternary cathode material precursor to the lithium source is in the range of 1:1 to 1:1.2.
[0022] By using the positive electrode material for lithium-ion secondary batteries and the preparation method thereof of the present invention, the cracking problem of secondary particles during the cycle process is avoided, thereby effectively improving the mechanical strength and structural stability of the ternary positive electrode material, while significantly improving the high-temperature cycle stability of the ternary positive electrode material and effectively reducing the impedance growth of the lithium-ion secondary battery prepared therefrom during the cycle process. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0024] Figure 1A , Figure 1B , Figure 1C , Figure 1D , Figure 1E , Figure 1F , Figure 1G , Figure 1H and Fig. 1I The SEM images of the positive electrode materials according to Examples 1 to 9 of the present invention are shown respectively, wherein Figure 1A :NCM98+0.25%WO3、 Figure 1B :NCM98+0.5%WO3、 Figure 1C :NCM98+1.0%WO3、 Figure 1D :NCM98+1.5%WO3、 Figure 1E :NCM98+2.0%WO3、 Figure 1F :NCM98+1.0%MO3、 Figure 1G :NCM98+1.0%Nb2O5、 Figure 1H :NCM811+0.5%WO3 and Fig. 1I :NCM92+0.5%WO3.
[0025] Figure 2 An SEM image of the positive electrode material of Comparative Example 1 (NCM98) is shown.
[0026] Figure 3 The XPS test results of the positive electrode material according to Example 3 of the present invention at different etching depths are shown.
[0027] Figure 4A and Figure 4B The STEM-EDS element line scan result of the positive electrode material according to Example 3 of the present invention is shown.
[0028] Figure 5 The results of measuring the primary particle size distribution of the positive electrode material according to Example 3 of the present invention are shown.
[0029] Figure 6 The measurement results of the primary particle size distribution of the positive electrode material of Comparative Example 1 are shown.
[0030] Figure 7 The hardness measurement results of Example 3 according to the present invention and Comparative Example 1 are shown.
[0031] Figure 8 A SEM image of a cross section of the positive electrode material according to Example 3 of the present invention after 100 cycles is shown.
[0032] Fig. 9 A SEM image of a cross section of the positive electrode material of Comparative Example 1 after 100 cycles is shown.
[0033] Fig.10 The graph shows the increase in charge transfer impedance of the battery according to Example 3 of the present invention after 100 cycles.
[0034] Fig.11 The increase in charge transfer impedance of the battery of Comparative Example 1 after 100 cycles is shown. DETAILED DESCRIPTION
[0035] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0036] As described in the background technology, the methods in the prior art cannot effectively modify the ternary positive electrode material to obtain the desired electrical properties and mechanical properties. Therefore, there is still a need to improve the method for preparing ternary positive electrode materials in the prior art. In view of the problems in the prior art, according to a typical embodiment of the present invention, a positive electrode material for a lithium-ion secondary battery is provided, the positive electrode material comprising polycrystalline particles of a ternary positive electrode material and a modified material, wherein the polycrystalline particles comprise a plurality of primary particles, and the modified material is located on the surface of the polycrystalline particles and / or on the grain boundary interface between the primary particles, and the modified material comprises an oxide of a transition metal with a positive valence of 5 or 6. In a preferred embodiment, the modified material of the present invention comprises tungsten oxide, niobium oxide or molybdenum oxide.
[0037] In the present invention, the ternary positive electrode material includes polycrystalline particles. As is well known in the art, polycrystalline particles refer to a structure composed of many primary grains, each of which has its own lattice and orientation. In the ternary positive electrode material of the present invention, the ternary positive electrode material first forms primary particles, and then a plurality of primary particles agglomerate to form polycrystalline particles. Different grains (primary particles in polycrystalline particles) will contact each other and form an interface. The interface formed is the grain boundary interface between the primary particles of the polycrystalline particles. In the present invention, the grain boundary interface is divided into internal grain boundaries and surface grain boundaries. The internal grain boundaries are connected by structural units (primary particles) of different directions or orientations, and exist in the polycrystalline particles of the entire ternary positive electrode material. The surface grain boundary is the edge area produced when a reaction occurs between the external environment and the surface of the material. In the present invention, the surface grain boundary is the grain boundary surface of the polycrystalline particle.
[0038] The use of unmodified polycrystalline materials (ternary positive electrode materials) in the prior art will cause the following problems: 1) intercrystalline or intracrystalline cracks in polycrystalline materials: the internal stress concentration of the material particles caused by the H2-H3 phase change during the charge and discharge process will cause intercrystalline or intracrystalline cracks in the material during the battery cycle, thereby causing the material performance to deteriorate; 2) interface degradation problems of polycrystalline materials: during the charge and discharge process of the battery, with the occurrence of side reactions, the polycrystalline material particles will inevitably break, and after the material is broken and damaged, the electrolyte will enter the interior of the positive electrode material, which will cause more side reactions between the positive electrode material and the electrolyte, exacerbating the degradation of the positive electrode material performance; 3) a decrease in thermal stability: for ultra-high nickel positive electrode materials, the side reactions between them and the electrolyte will not only affect the electrical properties of the material, but also the thermal stability of the positive electrode material will gradually deteriorate with the increase of nickel content.
[0039] In order to avoid the above problems, in the positive electrode material of the present invention, the modified material of the oxide of the transition metal containing positive 5 valence or positive 6 valence is enriched on the surface of the polycrystalline particles and the grain boundary interface between the primary particles. By adopting such a structure, the size, morphology and microstructure of the primary particles (single grain) of the positive electrode material are changed, and finally a ternary positive electrode material refined and densely stacked by primary particles is obtained. In addition, by introducing high-valent (positive 5 valence or positive 6 valence) transition metal elements such as tungsten, niobium or molybdenum, the primary particle size is refined and densely stacked, effectively changing the microstructure of the material, which can effectively alleviate the volume change of the ternary positive electrode material during lithium ion deintercalation, and the lower volume change avoids the cracking problem of the secondary particles during the cycle, thereby effectively improving the mechanical strength and structural stability of the ternary positive electrode material, while significantly improving the high temperature cycle stability of the ternary positive electrode material and effectively reducing the impedance growth of the lithium ion secondary battery prepared therefrom during the cycle.
[0040] In some embodiments of the present invention, the primary particles have a particle size of 400nm or less, preferably, the primary particles have a particle size of 100nm to 400nm; and the average particle size of the primary particles is in the range of 250nm to 350nm. The ternary positive electrode material is composed of primary particles having a particle size of 400nm or less. The particle size of the primary particles can be changed as needed, but should not exceed the scope of the present invention. For different embodiments, the particle size of the ternary positive electrode material can be in the following ranges: less than 400nm, less than 300nm, less than 200nm, less than 100nm, less than 50nm, 100nm to 400nm, 110nm to 390nm, 120nm to 380nm, 130nm to 370nm, 140nm to 360nm, 150nm to 350nm, 160nm to 340nm, 170nm to 330nm, 180nm to 320nm, 190nm to 310nm The average particle size of the primary particles may be in the range of 250nm to 350nm, 260nm to 340nm, 270nm to 330nm, 280nm to 320nm or 290nm to 310nm.
[0041] In some embodiments of the present invention, the average particle size of the primary particles is in the range of 250 nm to 350 nm. For different embodiments, the average particle size of the primary particles can be in the following range: 250nm to 350nm, 260nm to 340nm, 270nm to 330nm, 280nm to 320nm, 290nm to 310nm, 250nm to 340nm, 250nm to 330nm, 250nm to 320nm, 250nm to 310nm, 250nm to 300nm, 250nm to 290nm, 250nm to 280nm, 250nm to 270nm, 250nm to 260nm, 260nm to 350nm, 270nm to 350nm, 280nm to 350nm, 290nm to 350nm, 300nm to 350nm, 310nm to 350nm, 320nm to 350nm, 330nm to 350nm or 340nm to 350nm.
[0042] In some embodiments of the present invention, the ternary cathode material has a chemical general formula LiNi x Co y Mn 1-x-y O2, where 0.8 ≤ x < 1, 0 < y < 1 and 0 < x + y < 1; preferably 0.9 ≤ x < 1, 0 < y < 1 and 0 < x + y < 1. In the case of using the above general formula, the main ternary cathode material of the cathode material of the present invention belongs to a high-nickel cathode material. In the present invention, the high-nickel cathode material contains a relatively high content of nickel element. Usually, a nickel content exceeding 50% is a high-nickel cathode material, but in the present invention, the high-nickel cathode material used has a nickel content of more than 80%, preferably more than 90%. In the case of using the high-nickel cathode material, the cathode material of the present invention will have a higher energy density, thereby providing improved electrical performance for lithium-ion secondary batteries. Since the high-nickel cathode material has good chemical stability, it will maintain a low self-discharge rate when not in use, so it is not easy to have problems such as loss or aging. When the modified high-nickel cathode material of the present invention is used as the cathode material of a lithium-ion secondary battery, it exhibits excellent performance during repeated charge and discharge processes and can also maintain stability when the temperature changes.
[0043] In some embodiments of the present invention, the doping depth of the high-valence element contained in the modifying material in the cathode material is in the range of 0 nm to 20 nm. In the present invention, the modifying material is located on the surface of polycrystalline grains and / or at the grain boundary interfaces between primary grains. When the modifying material exists only on the surface of polycrystalline grains, its doping depth is 0 nm. When the modifying material exists both on the surface of polycrystalline grains and at the grain boundary interfaces between primary grains, it can be located at a depth of at most 20 nm from the ternary cathode material. For different embodiments, the doping depth of the high-valence element contained in the modifying material in the cathode material can be in the following ranges: 0 nm to 20 nm, 0 nm to 19 nm, 0 nm to 18 nm, 0 nm to 17 nm, 0 nm to 16 nm, 0 nm to 15 nm, 0 nm to 14 nm, 0 nm to 13 nm, 0 nm to 12 nm, 0 nm to 11 nm, 0 nm to 10 nm, 0 nm to 9 nm, 0 nm to 8 nm, 0 nm to 7 nm, 0 nm to 6 nm, 0 nm to 5 nm, 0 nm to 4 nm, 0 nm to 3 nm, 0 nm to 2 nm or 0 nm to 1 nm.
[0044] In different embodiments of the present invention, based on the total number of atoms of the positive electrode material, the doping amount of the transition metal in the positive electrode material is in the range of 0.25 atomic % to 2.1 atomic %. According to different embodiments, the doping amount of the modified material can be in the following ranges: 0.25 atomic % to 2.1 atomic %, 0.25 atomic % to 2.0 atomic %, 0.3 atomic % to 1.9 atomic %, 0.35 atomic % to 1.8 atomic %, 0.4 atomic % to 1.7 atomic %, 0.45 atomic % to 1.6 atomic %, 0.5 atomic % to 1.5 atomic %, 0.6 atomic % to 1.4 atomic %, 0.7 atomic % to 1.3 atomic %, 0.8 atomic % to 1.2 atomic %, 0.9 atomic % to 1.1 atomic %, 0.25 atomic % to 1 .5 atomic %, 0.25 atomic % to 1.0 atomic %, 0.25 atomic % to 0.5 atomic %, 0.3 atomic % to 2.1 atomic %, 0.35 atomic % to 2.1 atomic %, 0.4 atomic % to 2.1 atomic %, 0.45 atomic % to 2.1 atomic %, 0.5 atomic % to 2.1 atomic %, 0.6 atomic % to 2.1 atomic %, 0.7 atomic % to 2.1 atomic %, 0.8 atomic % to 2.1 atomic %, 0.9 atomic % to 2.1 atomic %, 1.0 atomic % to 2.1 atomic %, 1.5 atomic % to 2.1 atomic %.
[0045] According to another typical embodiment of the present invention, a method for preparing a positive electrode material for a lithium ion secondary battery is provided. The method comprises the following steps: step S1, sintering a lithium source, a ternary positive electrode material precursor and a modified material, wherein the modified material comprises an oxide of a transition metal with a positive valence of 5 or 6; step S2, grinding the product after the primary sintering, and performing a secondary sintering on the ground product, wherein the temperature of the primary sintering is lower than the secondary sintering temperature.
[0046] In the method of the present invention, a secondary sintering process is adopted to prepare polycrystalline particles. Different from the chemical vapor deposition method in the prior art or the preparation method of adding a tungsten source during the second sintering process, in the method of the present invention, a modifying material is first added during the high-temperature lithiation process (primary sintering) of the precursor of the ternary cathode material. The high-valence element oxide contained in the modifying material is doped on the surface of the polycrystalline particles of the ternary cathode material and / or at the grain boundary interface between primary particles, thereby changing the size, morphology and microstructure of the primary particles of the ternary cathode material, and finally obtaining a ternary cathode material with refined and densely packed primary particles. The cathode material prepared by the method of the present invention effectively changes the microstructure of the material, and this structure can effectively alleviate the volume change during the lithium ion insertion and extraction process of the ternary cathode material. The lower volume change avoids the cracking problem of secondary particles during the cycling process, thereby effectively improving the mechanical strength and structural stability of the ternary cathode material, while significantly enhancing the high-temperature cycling stability of the ternary cathode material and effectively reducing the impedance growth of the lithium ion secondary battery prepared therefrom during the cycling process.
[0047] In some embodiments of the present invention, the ternary cathode material has the chemical general formula LiNi x Co y Mn 1-x-y O2, where 0.8 ≤ x < 1, 0 < y < 1 and 0 < x + y < 1; preferably 0.9 ≤ x < 1, 0 < y < 1 and 0 < x + y < 1, and the precursor of the ternary cathode material is [Ni x Co y Mn 1-x-y (OH)2, where 0.8 ≤ x < 1, 0 < y < 1 and 0 < x + y < 1; preferably 0.9 ≤ x < 1, 0 < y < 1 and 0 < x + y < 1. In the case of using the above general formula, the main ternary cathode material of the cathode material of the present invention belongs to a high-nickel cathode material. In the present invention, the high-nickel cathode material contains a relatively high content of nickel element. Usually, a nickel content exceeding 50% is a high-nickel cathode material, but in the present invention, the high-nickel cathode material used has a nickel content of more than 80%, preferably more than 90%. In the case of using a high-nickel cathode material, the cathode material of the present invention will have a higher energy density, thereby providing improved electrical performance for the lithium ion secondary battery. Since the high-nickel cathode material has good chemical stability, it will maintain a low self-discharge rate when not in use, so it is not easy to have problems such as loss or aging. When the modified high-nickel cathode material of the present invention is used as the cathode material of a lithium ion secondary battery, it exhibits excellent performance during repeated charge and discharge processes and can also maintain stability when the temperature changes.
[0048] In the present invention, the modified materials for the modified ternary cathode material include but are not limited to tungsten oxide, niobium oxide or molybdenum oxide. By introducing oxides of high-valent transition metals tungsten, niobium or molybdenum, the primary particle size is refined and densely stacked, effectively changing the microstructure of the material.
[0049] In some embodiments of the present invention, the molar ratio of the ternary cathode material precursor to the modified material is in the range of 100:0.25 to 100:2.0. Within this range, the modified material can effectively form a modified material located on the grain boundary surface of the polycrystalline particles and / or the grain boundary interface between the primary particles during a single sintering process. For different embodiments, the molar ratio of the ternary cathode material precursor to the modified material can be in the following ranges: 100:0.25 to 100:1, 100:0.3 to 100:0.9, 100:0.35 to 100:0.8, 100:0.4 to 100:0.7, 100:0.45 to 100:0.6, 100:0.25 to 100:0.9, 100:0.25 to 100:0.8, 100:0. 0:0.25 to 100:0.7, 100:0.25 to 100:0.6, 100:0.25 to 100:0.5, 100:0.25 to 100:0.4, 100:0.25 to 100:0.3, 100:0.3 to 100:1, 100:0.35 to 100:1, 100:0.4 to 100:1, 100:0.45 to 100:1, 100:0.5 to 100 :1, 100:0.55 to 100:1, 100:0.6 to 100:1, 100:0.65 to 100:1, 100:0.7 to 100:1, 100:0.75 to 100:1, 100:0.8 to 100:1, 100:0.85 to 100:1, 100:0.9 to 100:1, 100:0.95 to 100:1, 100:0.25 to 100:2.0, 1 00:0.25 to 100:1.9, 100:0.25 to 100:1.8, 100:0.25 to 100:1.7, 100:0.25 to 100:1.6, 100:0.25 to 100:1.5, 100:0.25 to 100:1.4, 100:0.25 to 100:1.3, 100:0.25 to 100:1.3 or 100:0.25 to 100:1.1.
[0050] In a further embodiment of the present invention, the primary sintering can be performed at a temperature range of 450° C. to 600° C. for 4 to 7 hours, and oxygen is introduced at a flow rate of 80 ml / min to 150 ml / min during the primary sintering. In the present invention, the sintering temperature, sintering time and amount of oxygen introduced in the primary sintering can be selected separately. In different embodiments, the sintering temperature of the primary sintering may be in the range of 450°C to 600°C, 460°C to 590°C, 470°C to 580°C, 480°C to 570°C, 490°C to 560°C, 500°C to 550°C, 510°C to 540°C, 520°C to 530°C, 450°C to 580°C, 450°C to 560°C, 450°C to 540°C, 450°C to 520°C, 450°C to 500°C, 450°C to 480°C, 450°C to 460°C, 470°C to 600°C, 490°C to 600°C, 510°C to 600°C, 530°C to 600°C, 550°C to 600°C, 570°C to 600°C, or 590°C to 600°C. The sintering time for the primary sintering process can be selected from the following ranges: 4 to 7 hours, 4.5 to 6.5 hours, 5 to 6 hours, 4.5 to 7 hours, 5 to 7 hours, 5.5 to 7 hours, 6 to 7 hours, 6.5 to 7 hours, 4 to 6.5 hours, 4 to 6 hours, 4 to 5.5 hours, 4 to 5 hours or 4 to 4.5 hours. The flow rate of oxygen introduced during the primary sintering process can be in the following range: 80ml / min to 150ml / min, 90ml / min to 140ml / min, 100ml / min to 130ml / min, 110ml / min to 120ml / min, 80ml / min to 140ml / min, 80ml / min to 130ml / min, 80ml / min to 120ml / min, 80ml / min to 110ml / min, 80ml / min to 100ml / min, 80ml / min to 90ml / min, 90ml / min to 150ml / min, 100ml / min to 150ml / min, 110ml / min to 150ml / min, 120ml / min to 150ml / min, 130ml / min to 150ml / min, or 140ml / min to 150ml / min.
[0051] In some embodiments, the secondary sintering is performed at a temperature range of 700° C. to 800° C. for 12 to 20 hours, and oxygen is introduced at a flow rate of 80 ml / min to 150 ml / min during the secondary sintering. In the present invention, the sintering temperature, sintering time and amount of oxygen introduced in the secondary sintering can be selected separately. In different embodiments, the sintering temperature of the secondary sintering may be in the range of 700°C to 800°C, 710°C to 790°C, 720°C to 780°C, 730°C to 770°C, 740°C to 760°C, 710°C to 800°C, 720°C to 800°C, 730°C to 800°C, 740°C to 800°C, 750°C to 800°C, 760°C to 800°C, 770°C to 800°C, 780°C to 800°C, 790°C to 800°C, 700°C to 790°C, 700°C to 780°C, 700°C to 770°C, 700°C to 760°C, 700°C to 750°C, 700°C to 740°C, 700°C to 730°C, 700°C to 720°C, and 700°C to 710°C. The sintering time for the secondary sintering process can be selected from the following ranges: 12 to 20 hours, 13 to 19 hours, 14 to 18 hours, 15 to 17 hours, 12 to 19 hours, 12 to 18 hours, 12 to 17 hours, 12 to 16 hours, 12 to 15 hours, 12 to 14 hours, 12 to 13 hours, 13 to 20 hours, 14 to 20 hours, 15 to 20 hours, 16 to 20 hours, 17 to 20 hours, 18 to 20 hours, or 19 to 20 hours. The flow rate of oxygen introduced during the secondary sintering process can be in the following range: 80ml / min to 150ml / min, 90ml / min to 140ml / min, 100ml / min to 130ml / min, 110ml / min to 120ml / min, 80ml / min to 140ml / min, 80ml / min to 130ml / min, 80ml / min to 120ml / min, 80ml / min to 110ml / min, 80ml / min to 100ml / min, 80ml / min to 90ml / min, 90ml / min to 150ml / min, 100ml / min to 150ml / min, 110ml / min to 150ml / min, 120ml / min to 150ml / min, 130ml / min to 150ml / min, or 140ml / min to 150ml / min.
[0052] In the method of the present invention, any material capable of providing lithium element can be used as a lithium source, and preferred lithium sources include lithium hydroxide (lithium hydroxide monohydrate) or lithium carbonate.
[0053] In a further embodiment of the present invention, the molar ratio of the ternary cathode material precursor to the lithium source is in the range of 1:1 to 1:1.2. According to different embodiments, the molar ratio of the ternary cathode material precursor to the lithium source is in the following ranges: 1:1 to 1:1.2, 1:11 to 1:1.19, 1:12 to 1:1.18, 1:13 to 1:1.17, 1:14 to 1:1.16, 1:1 to 1:1.19, 1:1 to 1:1.18, 1:1 to 1:1.17, 1:1 to 1:1.16, 1:1 to 1:1.15, 1:1 to 1:1.14, 1:1 to 1:1.13, 1:1 to 1:1.12, 1:1 to 1:1.11, 1:11 to 1:1.2, 1:12 to 1:1.2, 1:13 to 1:1.2, 1:14 to 1:1.2, 1:15 to 1:1.2, 1:16 to 1:1.2, 1:17 to 1:1.2, 1:18 to 1:1.2, or 1:19 to 1:1.2.
[0054] The present invention is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed by the present invention.
[0055] Example 1
[0056] Preparation of cathode materials
[0057] 3g Ni 0.98 Co 0.01 Mn 0.01 (OH)2 precursor, 1.47g lithium hydroxide monohydrate (the molar ratio of precursor to lithium hydroxide monohydrate is = 1:1.06) and 0.0188g tungsten oxide (WO3, the molar ratio of precursor to tungsten oxide is 100:0.25) are mixed evenly in an agate mortar. First, the mixture is sintered in a 500℃ tube furnace for 5h, the heating rate is 3℃ / min, and high-purity oxygen is introduced, and the oxygen flow rate is 100mL / min. After the first sintering is completed, the temperature is naturally lowered, and when the furnace temperature drops to room temperature, the material after the first sintering is taken out. The material after the first sintering is ground in an agate mortar for 5min, and then placed in a 720℃ tube furnace for 15h, the heating rate is 3℃ / min, and the oxygen flow rate is 100mL / min. After the secondary sintering is completed, the temperature is naturally lowered. When the furnace body drops to room temperature, the secondary sintered material is taken out, ground in an agate mortar for 5 minutes, and then sealed and transferred to a glove box for storage, thereby obtaining the positive electrode material.
[0058] Preparation of batteries
[0059] Preparation of positive electrode
[0060] 0.2125g of the above-prepared positive electrode material and 0.0175g of graphite conductive agent were dispersed in 0.4g of N-methylpyrrolidone (containing 5% polyvinylidene fluoride) to obtain a positive electrode mixture slurry. Subsequently, the positive electrode mixture slurry was coated on an aluminum foil to obtain a positive electrode collector. The positive electrode collector was dried by baking at 110°C for 1h. After rolling, a small disc-shaped positive electrode sheet of 11.3mm was cut by a stamping process.
[0061] Preparation of electrolyte
[0062] 15.0 g of ethylene carbonate, 70.0 g of dimethyl carbonate, and 15.0 g of lithium hexafluorophosphate were mixed to prepare an electrolyte solution.
[0063] Battery Assembly
[0064] Assemble 2032 button cells in a glove box. Use the positive electrode obtained in the above steps as the positive electrode, and the negative electrode as lithium metal. Assemble the positive electrode, negative electrode, separator and battery shell of the button cell and inject electrolyte. After the battery is assembled, let it stand for about 5 hours to age, thereby obtaining a nickel cobalt manganese oxide lithium button cell.
[0065] Example 2
[0066] Preparation of cathode materials
[0067] 3g Ni 0.98 Co 0.01 Mn 0.01 (OH)2 precursor, 1.47g lithium hydroxide monohydrate (the molar ratio of precursor to lithium hydroxide monohydrate is = 1:1.06) and 0.0376g tungsten oxide (WO3, the molar ratio of precursor to tungsten oxide is 100:0.5) are mixed evenly in an agate mortar. First, the mixture is sintered in a tube furnace at 500℃ for 5h, the heating rate is 3℃ / min, and high-purity oxygen is introduced, and the oxygen flow rate is 100mL / min. After the first sintering is completed, the temperature is naturally lowered, and when the furnace temperature drops to room temperature, the material after the first sintering is taken out. The material after the first sintering is ground in an agate mortar for 5min, and then placed in a tube furnace at 720℃ for 15h again, the heating rate is 3℃ / min, and the oxygen flow rate is 100mL / min. After the second sintering is completed, the temperature is naturally lowered, and when the furnace body drops to room temperature, the second sintered material is taken out, ground in an agate mortar for 5min, and then sealed and transferred to a glove box for storage. Thus, a positive electrode material is obtained.
[0068] Preparation of batteries
[0069] The 2032 button cell was prepared in the same manner as in Example 1.
[0070] Example 3
[0071] Preparation of cathode materials
[0072] 3g Ni 0.98 Co 0.01 Mn 0.01 (OH)2 precursor, 1.47g lithium hydroxide monohydrate (the molar ratio of precursor to lithium hydroxide monohydrate is = 1:1.06) and 0.0751g tungsten oxide (WO3, the molar ratio of precursor to tungsten oxide is 100:1.0) are mixed evenly in an agate mortar. First, the mixture is sintered in a tube furnace at 500℃ for 5h, the heating rate is 3℃ / min, and high-purity oxygen is introduced, and the oxygen flow rate is 100mL / min. After the first sintering is completed, the temperature is naturally lowered, and when the furnace temperature drops to room temperature, the material after the first sintering is taken out. The material after the first sintering is ground in an agate mortar for 5min, and then placed in a tube furnace at 720℃ for 15h again, the heating rate is 3℃ / min, and the oxygen flow rate is 100mL / min. After the second sintering is completed, the temperature is naturally lowered, and when the furnace body drops to room temperature, the second sintered material is taken out, ground in an agate mortar for 5min, and then sealed and transferred to a glove box for storage. Thus, a positive electrode material is obtained.
[0073] Preparation of batteries
[0074] The 2032 button cell was prepared in the same manner as in Example 1.
[0075] Example 4
[0076] Preparation of cathode materials
[0077] 3g Ni 0.98 Co 0.01 Mn 0.01 (OH)2 precursor, 1.47g lithium hydroxide monohydrate (the molar ratio of precursor to lithium hydroxide monohydrate is 1:1.06) and 0.1128g tungsten oxide (WO3, the molar ratio of precursor to tungsten oxide is 100:1.5) are mixed evenly in an agate mortar. First, the mixture is sintered in a 500℃ tube furnace for 5h, the heating rate is 3℃ / min, and high-purity oxygen is introduced, and the oxygen flow rate is 100mL / min. After the first sintering is completed, the temperature is naturally lowered, and when the furnace temperature drops to room temperature, the material after the first sintering is taken out. The material after the first sintering is ground in an agate mortar for 5min, and then placed in a 720℃ tube furnace for 15h again, the heating rate is 3℃ / min, and the oxygen flow rate is 100mL / min. After the second sintering is completed, the temperature is naturally lowered, and when the furnace body drops to room temperature, the second sintered material is taken out, ground in an agate mortar for 5min, and then sealed and transferred to a glove box for storage. Thus, a positive electrode material is obtained.
[0078] Preparation of batteries
[0079] The 2032 button cell was prepared in the same manner as in Example 1.
[0080] Example 5
[0081] Preparation of cathode materials
[0082] 3g Ni 0.98 Co 0.01 Mn 0.01 (OH)2 precursor, 1.47g lithium hydroxide monohydrate (the molar ratio of precursor to lithium hydroxide monohydrate is = 1:1.06) and 0.1502g tungsten oxide (WO3, the molar ratio of precursor to tungsten oxide is 100:2.0) are mixed evenly in an agate mortar. First, the mixture is sintered in a tube furnace at 500℃ for 5h, the heating rate is 3℃ / min, and high-purity oxygen is introduced, and the oxygen flow rate is 100mL / min. After the first sintering is completed, the temperature is naturally lowered, and when the furnace temperature drops to room temperature, the material after the first sintering is taken out. The material after the first sintering is ground in an agate mortar for 5min, and then placed in a tube furnace at 720℃ for 15h again, the heating rate is 3℃ / min, and the oxygen flow rate is 100mL / min. After the second sintering is completed, the temperature is naturally lowered, and when the furnace body drops to room temperature, the second sintered material is taken out, ground in an agate mortar for 5min, and then sealed and transferred to a glove box for storage. Thus, a positive electrode material is obtained.
[0083] Preparation of batteries
[0084] The 2032 button cell was prepared in the same manner as in Example 1.
[0085] Example 6
[0086] Preparation of cathode materials
[0087] 3g Ni 0.98 Co 0.01 Mn 0.01(OH)2 precursor, 1.47g lithium hydroxide monohydrate (the molar ratio of precursor to lithium hydroxide monohydrate is = 1:1.06) and 0.0466g molybdenum oxide (MoO3, the molar ratio of precursor to molybdenum oxide is 100:1.0) are mixed evenly in an agate mortar. First, the mixture is sintered in a tube furnace at 500℃ for 5h, the heating rate is 3℃ / min, and high-purity oxygen is introduced, and the oxygen flow rate is 100mL / min. After the first sintering is completed, the temperature is naturally lowered, and when the furnace temperature drops to room temperature, the material after the first sintering is taken out. The material after the first sintering is ground in an agate mortar for 5min, and then placed in a tube furnace at 720℃ for 15h again, the heating rate is 3℃ / min, and the oxygen flow rate is 100mL / min. After the second sintering is completed, the temperature is naturally lowered, and when the furnace body drops to room temperature, the second sintered material is taken out, ground in an agate mortar for 5min, and then sealed and transferred to a glove box for storage. Thus, a positive electrode material is obtained.
[0088] Preparation of batteries
[0089] The 2032 button cell was prepared in the same manner as in Example 1.
[0090] Example 7
[0091] Preparation of cathode materials
[0092] 3g Ni 0.98 Co 0.01 Mn 0.01 (OH)2 precursor, 1.47g lithium hydroxide monohydrate (the molar ratio of precursor to lithium hydroxide monohydrate is 1:1.06) and 0.0861g niobium oxide (Nb2O5, the molar ratio of precursor to niobium oxide is 100:1.0) are mixed evenly in an agate mortar. First, the mixture is sintered in a tube furnace at 500℃ for 5h, with a heating rate of 3℃ / min, and high-purity oxygen is introduced with an oxygen flow rate of 100mL / min. After the first sintering is completed, the temperature is naturally lowered, and when the furnace temperature drops to room temperature, the material after the first sintering is taken out. The material after the first sintering is ground in an agate mortar for 5min, and then placed in a tube furnace at 720℃ for 15h, with a heating rate of 3℃ / min and an oxygen flow rate of 100mL / min. After the secondary sintering is completed, the temperature is naturally lowered. When the furnace body is cooled to room temperature, the secondary sintered material is taken out, ground in an agate mortar for 5 minutes, and then sealed and transferred to a glove box for storage. Thus, the positive electrode material is obtained.
[0093] Preparation of batteries
[0094] The 2032 button cell was prepared in the same manner as in Example 1.
[0095] Example 8
[0096] Preparation of cathode materials
[0097] 3g Ni 0.80 Co 0.10 Mn 0.10 (OH)2 precursor, 1.47g lithium hydroxide monohydrate (the molar ratio of precursor to lithium hydroxide monohydrate is = 1:1.06) and 0.0376g tungsten oxide (WO3, the molar ratio of precursor to tungsten oxide is 100:0.5) are mixed evenly in an agate mortar. First, the mixture is sintered in a 500℃ tube furnace for 5h, the heating rate is 3℃ / min, and high-purity oxygen is introduced, and the oxygen flow rate is 100mL / min. After the first sintering is completed, the temperature is naturally lowered, and when the furnace temperature drops to room temperature, the material after the first sintering is taken out. The material after the first sintering is ground in an agate mortar for 5min, and then placed in a 700℃ tube furnace for 15h again, the heating rate is 3℃ / min, and the oxygen flow rate is 100mL / min. After the second sintering is completed, the temperature is naturally lowered, and when the furnace body drops to room temperature, the second sintered material is taken out, ground in an agate mortar for 5min, and then sealed and transferred to a glove box for storage. Thus, a positive electrode material is obtained.
[0098] Preparation of batteries
[0099] The 2032 button cell was prepared in the same manner as in Example 1.
[0100] Example 9
[0101] Preparation of cathode materials
[0102] 3g Ni 0.92 Co 0.04 Mn 0.04 (OH)2 precursor, 1.47g lithium hydroxide monohydrate (the molar ratio of precursor to lithium hydroxide monohydrate is = 1:1.06) and 0.0376g tungsten oxide (WO3, the molar ratio of precursor to tungsten oxide is 100:0.5) are mixed evenly in an agate mortar. First, the mixture is sintered in a 500℃ tube furnace for 5h, the heating rate is 3℃ / min, and high-purity oxygen is introduced, and the oxygen flow rate is 100mL / min. After the first sintering is completed, the temperature is naturally lowered, and when the furnace temperature drops to room temperature, the material after the first sintering is taken out. The material after the first sintering is ground in an agate mortar for 5min, and then placed in a 700℃ tube furnace for 15h again, the heating rate is 3℃ / min, and the oxygen flow rate is 100mL / min. After the second sintering is completed, the temperature is naturally lowered, and when the furnace body drops to room temperature, the second sintered material is taken out, ground in an agate mortar for 5min, and then sealed and transferred to a glove box for storage. Thus, a positive electrode material is obtained.
[0103] Preparation of batteries
[0104] The 2032 button cell was prepared in the same manner as in Example 1.
[0105] Comparative Example 1
[0106] Preparation of cathode materials
[0107] 3g Ni 0.98 Co 0.01 Mn 0.01 The (OH)2 precursor and 1.47g of lithium hydroxide monohydrate (the molar ratio of the precursor to lithium hydroxide monohydrate is = 1:1.06) are mixed evenly in an agate mortar. First, the mixture is sintered in a tube furnace at 500°C for 5h, with a heating rate of 3°C / min, and high-purity oxygen is introduced with an oxygen flow rate of 100mL / min. After the first sintering is completed, the temperature is naturally lowered, and when the furnace temperature drops to room temperature, the material after the first sintering is taken out. The material after the first sintering is ground in an agate mortar for 5min, and then placed in a tube furnace at 720°C for 15h, with a heating rate of 3°C / min and an oxygen flow rate of 100mL / min. After the second sintering is completed, the temperature is naturally lowered, and when the furnace body drops to room temperature, the second sintered material is taken out, ground in an agate mortar for 5min, and then sealed and transferred to a glove box for storage. Thus, the positive electrode material NCM98 is obtained.
[0108] Preparation of batteries
[0109] The 2032 button cell was prepared in the same manner as in Example 1.
[0110] Battery performance test
[0111] First charge and discharge specific capacity (mAh g -1 ) and determination of specific capacity after 100 cycles
[0112] The batteries prepared in the above examples and comparative examples were tested. At 30°C and a voltage range of 2.0-4.25V, the batteries were cycled once, with the charge and discharge currents both being 0.1C (20mA g -1 ). The battery was then cycled 100 times at 60°C and in the voltage range of 2.5-4.25V, with charge and discharge currents of 1C and 5C, respectively.
[0113] The experimental results are shown in Table 1.
[0114] Determination of the first cycle coulombic efficiency
[0115] The initial efficiency of the lithium-ion secondary batteries produced in each embodiment and each comparative example is calculated by the following formula:
[0116] First efficiency = first discharge capacity / first charge capacity × 100%.
[0117] The experimental results are shown in Table 1.
[0118] Cathode material composition determination
[0119] The compositions of the positive electrode materials prepared in the above examples and comparative examples were analyzed and measured. The compositions were measured using an inductively coupled plasma optical emission spectrometer (ICP-OES), and the test results are shown in Table 2.
[0120] Microscopic analysis of cathode materials
[0121] SEM (SEM test instrument manufacturer: Zeiss, model: SUPRA55 SAPPHIRE) was used to generate images of the positive electrode materials prepared in the above embodiment and comparative example, and the image results are as follows: FIG. 1A to FIG. 1I as well as Figure 2 shown.
[0122] Distribution analysis of modified materials in the bulk phase of cathode materials
[0123] XPS (XPS test instrument manufacturer: Thermo Fisher, model: Escalab Xi+) was used to analyze the positive electrode material prepared in Example 3. The results are as follows: Figure 3 As shown, STEM was used to observe and test the weight distribution of elements in the positive electrode material prepared in Example 3. The experimental results are shown in FIG4 .
[0124] Particle size analysis
[0125] The particle sizes of the positive electrode materials prepared in Example 3 and Comparative Example 1 were analyzed respectively, the particle size distribution measurement software was Nano measure, and the particle size was observed by SEM. The SEM image of Example 3 is as follows: Figure 1C As shown, the SEM image of Comparative Example 1 is as follows Figure 2 The particle size distribution test results are shown in Figure 5 and Figure 6 shown.
[0126] Mechanical strength analysis
[0127] The hardness of the positive electrode materials prepared in Example 3 and Comparative Example 1 was analyzed using a micro compression tester (micro compression tester manufacturer: Shimadzu, model: MCT-510). Figure 7 shown.
[0128] The batteries prepared in Example 3 and Comparative Example 1 were subjected to the cycle test described above, and the cycle was stopped after 100 cycles, wherein the cycle conditions were: 60°C, 1C charge, 5C discharge, 2.5-4.25V, 100 cycles. The batteries prepared in Example 3 and Comparative Example 1 were disassembled to obtain the positive electrode materials, and then the positive electrode materials after 100 cycles were observed using SEM (SEM test instrument manufacturer: Zeiss, model: SUPRA55SAPPHIRE). The results are as follows Figure 8 and Fig. 9 shown.
[0129] Impedance test
[0130] The impedance test was performed on the batteries prepared in Example 3 and Comparative Example 1 using an EIS test instrument (EIS test instrument manufacturer: Shanghai Chenhua, model: CHI760E), wherein the rated cycle conditions of the batteries were: 60°C, 1C charge, 5C discharge, 2.5-4.25V cycle 100 cycles, and the experimental conditions of the impedance test were: room temperature, battery voltage of about 4.25V, frequency of 10 -3 Hz to 10 5 Hz. The experimental results are as follows Fig.10 and Fig.11 shown.
[0131] Table 1
[0132]
[0133] It can be seen from the experimental results shown in Table 1 above that when the positive electrode material is prepared by the method of the present invention, the first cycle coulomb efficiency and the capacity after 100 cycles of the battery are significantly improved. By comparing Examples 1-5, it can be seen that when 1.0 mol% of tungsten oxide is added, the first cycle coulomb efficiency of the battery can reach 96.1%, and its capacity after 100 cycles can reach an astonishing 190 mAh g -1 Compared with comparative example 1 (without adding dopant), the first cycle coulombic efficiency or the capacity after 100 cycles of the battery of the present invention is significantly improved.
[0134] Table 2
[0135]
[0136] Table 2 shows the elemental composition of the positive electrode materials of Examples 1-9 and Comparative Example 1, wherein, through ICP-OES analysis of the positive electrode materials prepared in Examples 1 to 9, it can be seen that the doping amount of the transition metal (W, Mo or Nb) is in the range of about 0.25 atomic % to about 2 atomic %.
[0137] from FIG. 1A to FIG. 1IIt can be seen from the SEM results that the positive electrode material of the present invention contains multiple primary particles, and these primary particles are agglomerated into polycrystalline particle spheres. Figure 2 The SEM image of the positive electrode material prepared in Comparative Example 1 is shown in Figure 2 and FIG. 1A to FIG. 1I It can be clearly seen from the comparison that the primary particles of the positive electrode material of the present invention have a smaller size.
[0138] Figure 3 The XPS test results of the positive electrode material prepared in Example 3 of the present invention are shown, wherein the positive electrode material in Example 3 is doped with 1% tungsten oxide. It can be seen from the XPS results that the tungsten element ( Figure 3 (indicated by the two vertical lines in the figure) obvious peaks appear on the surface of the positive electrode material and at 5nm, 10nm, and 20nm, but no characteristic peak appears at 30nm. Therefore, it can be determined that the doping depth of the transition metal (such as tungsten element) of the present invention is in the range of 0nm to 20nm. Figure 4B The STEM-EDS element line scan results of the positive electrode material according to Example 3 of the present invention are shown. Figure 4A It can be seen that the scan is performed from grain boundary 1 to grain boundary 2 along the scan line. Figure 4B It can be seen that two grain boundary peaks appear at grain boundary 1 and grain boundary 2. In the two grain boundary peaks, the content of tungsten is significantly higher than that at other positions, indicating that W is enriched at the grain boundary. Therefore, it can be shown that in the positive electrode material of the present invention, the modified material (such as tungsten) is enriched on the grain boundary interface between the primary particles.
[0139] Figure 5 The results of measuring the primary particle size distribution of the positive electrode material according to Example 3 of the present invention are shown. Figure 6 The primary particle size distribution measurement results of the positive electrode material of Comparative Example 1 are shown. Figure 5 and Figure 6 The results and reference Figure 1C and Figure 2 It can be seen that about 90% of the primary particles in the positive electrode material of the present invention have a size in the range of 200nm to 400nm, of which about 47% of the primary particles have a size in the range of 200nm to 300nm, about 35% of the primary particles have a size in the range of 300nm to 400nm, and the average particle size of the primary particles is about 290nm; while in the positive electrode material of Comparative Example 1 to which no modifying material is added, about 96% of the primary particles have a size between 300nm and 900nm, of which more than about 90% of the primary particles have a particle size of more than 400nm (much larger than the range of less than 400nm in the present application), and the average particle size of the primary particles is 600nm.
[0140] Figure 7The hardness measurement results of Example 3 according to the present invention and Comparative Example 1 are shown. The average particle hardness of the positive electrode material of Example 3 of the present invention (1% doping amount) is 104 MPa, while the average particle hardness of the undoped Comparative Example 1 is 68 MPa, and the hardness of the positive electrode material is increased by about 50%. Figure 8 and Fig. 9 It can also be seen from the SEM image of the material cross section that after 100 cycles of the grains, the structural integrity of the positive electrode material of Example 3 of the present invention is well maintained without obvious deformation or decomposition, while the positive electrode material of Comparative Example 1 has already experienced serious particle breakage.
[0141] Fig.10 The graph shows the increase in charge transfer impedance of the battery according to Example 3 of the present invention after 100 cycles. Fig.11 The increase in charge transfer impedance of the battery of Comparative Example 1 after 100 cycles is shown. Fig.11 The charge transfer impedance (R ct ) increased by nearly 3 times (from 55Ω to 215Ω), while the charge transfer impedance (R ct ) only increased by 10% (from 80Ω to 88Ω). Since the impedance value of the positive electrode material of the present invention is significantly reduced after cycling, it can ensure the high capacity of the battery after 100 cycles.
[0142] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A positive electrode material for a lithium ion secondary battery, characterized in that: include: Polycrystalline particles of ternary cathode materials, including multiple primary particles; as well as The modifying material is located on the surface of the polycrystalline particles and / or on the grain boundary interface between the primary particles, and the modifying material comprises an oxide of a transition metal with a positive valence of five or six.
2. The positive electrode material according to claim 1, characterized in that The modified material comprises tungsten oxide, niobium oxide or molybdenum oxide.
3. The positive electrode material according to claim 1, characterized in that The primary particles have a particle size of 400 nm or less.
4. The positive electrode material according to claim 1, characterized in that The average particle diameter of the primary particles is in the range of 250 nm to 350 nm.
5. The positive electrode material according to claim 1, characterized in that The ternary cathode material has a chemical general formula LiNi x Co y Mn 1-x-y O2, where 0.8 ≤ x < 1, 0 < y < 1 and 0 < x + y < 1; preferably 0.9 ≤ x < 1, 0 < y < 1 and 0 < x + y < 1.
6. The positive electrode material according to claim 1, characterized in that The doping depth of the modified material is in the range of 0 nm to 20 nm.
7. The positive electrode material according to claim 1, characterized in that The doping amount of the transition metal in the positive electrode material is in the range of 0.25 atomic % to 2.1 atomic % based on the total atomic number of the positive electrode material.
8. A method for preparing a positive electrode material for a lithium ion secondary battery, characterized in that: The following steps are involved: Step S1, sintering a lithium source, a ternary cathode material precursor and a modified material, wherein the modified material comprises an oxide of a transition metal with a positive valence of five or six; Step S2, grinding the product after the primary sintering, and performing secondary sintering on the ground product, wherein the temperature of the primary sintering is lower than the temperature of the secondary sintering.
9. The method according to claim 8, characterized in that The ternary cathode material precursor is [Ni x Co y Mn 1-x-y (OH)2, where 0.8 ≤ x < 1, 0 < y < 1 and 0 < x + y < 1; preferably 0.9 ≤ x < 1, 0 < y < 1 and 0 < x + y < 1.
10. The method according to claim 8, characterized in that The modified material comprises tungsten oxide, niobium oxide or molybdenum oxide.
11. The method according to claim 8, characterized in that The molar ratio of the ternary cathode material precursor to the modified material is in the range of 100:0.25 to 100:2.
0.
12. The method according to claim 8, characterized in that The primary sintering is performed at a temperature ranging from 450° C. to 600° C. for 4 to 7 hours, and oxygen is introduced at a flow rate of 80 ml / min to 150 ml / min during the primary sintering.
13. The method according to claim 8, characterized in that The secondary sintering is performed at a temperature range of 700° C. to 800° C. for 12 to 20 hours, and oxygen is introduced at a flow rate of 80 ml / min to 150 ml / min during the secondary sintering.
14. The method according to claim 8, characterized in that The lithium source includes lithium hydroxide or lithium carbonate.
15. The method according to claim 8, characterized in that The molar ratio of the ternary cathode material precursor to the lithium source is in the range of 1:1 to 1:1.2.
